Exploring the Research Focus of RNA-Binding Proteins in Trauma and Burns - Sujie Xie; Yifan Liu; Wei Zhang; Jianyu Lu; Xirui Tong; Jie Huang; Yushu Zhu; Minjuan Wu; Xinya Guo; Hanlin Sun; Minyi Gu; Luofeng Jiang; et al. (Analytical Cellular Pathology)
Conclusion: Our findings provide valuable insights into the developing trends and key areas of research on RBPs in trauma and burns. Notably, we identified two primary hotspots: RBPs in the pathophysiological mechanisms of various traumatic injuries and RBPs in the processes of cutaneous wound healing. This rapidly evolving field offers significant reference points for scientific researchers and clinical practitioners.